Biochemical and microbiological quality of fermented silage prepared from dressing waste of Indian major carps using different concentrations of jaggery - Tanuja, S.; Kumar, Anil; Sarkar, A.; Nayak, Sujit K. (Indian Journal of Fisheries, 2016)
Present study investigated the shelf life of fermented silage prepared from dressing waste (gut and gills) of Indian major carps and the effect of different concentrations of jaggery as carbohydrate source, on the biochemical and microbiological changes in the silage. Fermented silage was prepared using jaggery at 10% w/w (F1) and 20% w/w (F2) concentrations. F2 had a lower crude fat and ash content. The lowest pH attained was 4.11 and 4.02 in F1 and F2 respectively by the end of 15 days. Significantly higher (p